Формирование тарифов на поставляемый в Армению российский природный газ в условиях евразийской интеграции - В. С. Давтян (ՀՀ ԳԱԱ հրատ.)
Հայաստան մատակարարվող ռուսական բնական գազի սակագների գոյացման խնդիրների ուսումնասիրությունը հույժ կարևոր է, քանի որ դրանք անմիջականորեն ազդում են ՀՀ տնտեսական արդյունավետության, քաղաքացիների բարեկեցության և, հետևաբար, ներքաղաքական կայունության վրա: The study of the problems of forming tariffs for the Russian natural gas supplied to Armenia is extremely important because of its direct impact on the level of efficiency of the economic system of the Republic of Armenia, the welfare of its citizens and, consequently, domestic political sustainability.
Keywords: H Social Sciences; Economic Theory